Results and Performance of the World Bank Group 2017 : An Independent Evaluation - Independent Evaluation Group (World Bank, Washington, DC, 2018)
The Results and Performance of the World Bank Group (RAP) report is an annual review by the Independent Evaluation Group (IEG) of the development effectiveness of the World Bank Group. The RAP covers the World Bank (International Bank for Reconstruction and Development and International Development Association), the International Finance Corporation, and the Multilateral Investment Guarantee Agency (four of the five institutions of the World Bank Group). The report synthesizes existing evidence from IEG evaluations, validations, and engagements, complemented by analysis of relevant information from other sources (for example, World Bank Group documents). Results and performance are assessed separately for each of the institutions because of their differing time frames, operating models, and clients. The theme this year is environmental sustainability, focusing on selected questions related to the contribution of the World Bank Group to environmental sustainability (chapter 1). This RAP (i) assesses the extent to which the World Bank Group portfolio includes activities that support environmental sustainability (and changes over a 10-year period), (ii) takes stock of how the World Bank Group is measuring its contribution to environmental sustainability, and (iii) presents analysis on the World Bank Group’s systems for managing environmental and social risks. The RAP does not seek to provide an overall assessment of the environmental effects of the World Bank Group’s projects because data are available only for the subset of projects where environmental goals were the primary objective.